Gender grading bias at Stockholm University: Quasi-experimental evidence from an anonymous grading reform - Joakim Jansson; Björn Tyrefors Hinnerich (Research Institute of Industrial Economics (IFN), 2018)
In this paper, we first present novel evidence of grading bias against women at the university level. This is in contrast to previous results at the secondary education level. Contrary to the gender composition at lower levels of education in Sweden, the teachers and graders at the university level are predominantly male. Thus, an in-group bias mechanism could consistently explain the evidence from both the university and secondary education level. However, we find that in-group bias can only explain approximately 20 percent of the total grading bias effect at the university level.
Keywords: I23; J16; 330; Grading bias; University; Discrimination; Education; Anonymous grading